Dephosphorylation of a major sperm membrane protein is induced by egg jelly during sea urchin fertilization - Ward, Gary E. (1983)
A 160-kilodalton (kDa) protein of Arbacia punctulata sperm is constitutively phosphorylated on serine residues, as shown by in vivo(32)PO(4)(3-) labeling. Exposure of sperm to solubilized egg jelly results in the immediate dephosphorylation (within 5 sec) of this protein and a simultaneous increase in its electrophoretic mobility (to an apparent molecular mass of 150 kDa). In its dephosphorylated form (150 kDa), the protein is a major component of the flagellar plasma membrane. In fact, silver-stained polyacrylamide gels show the 160/150-kDa protein to be the third most abundant protein in the whole flagellum. The spermatozoan must pass through the egg jelly layer on its way to the egg surface. The jelly-induced dephosphorylation of such an abundant sperm membrane protein may be an important event in the successful interaction of sperm and egg during fertilization.